STUDENTS' CREATIVITY IN THE IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNING (CTL) IN LEARNING NEWTON'S THIRD LAW OF MOTION - Menurseto Mawaddah, - (2018)
This research investigated students' creativity in the implementation of Contextual Teaching and Learning (CTL) in learning Newton's Third Law of motion. The method of this research was weak experiment which was implemented to 24 students of grade VIII in International School. The data of students' creativity collected from rubric scoring of Creative Product Analysis Matrix (CPAM) and the data of students' response used questionnaire. Data analysis showed that the students experience CTL in the learning Newton's Third Law of motion. Furthermore, the result of students' creativity was in fair categorize. Students' response toward implementation of CTL showed positive response in all indicators. It indicates that the implementation of CTL is suitable for the student to learn Newton's third law and it can trigger students' creativity in secondary school student.;---Penelitian ini menginvestigasi kreativitas siswa pada implementasi Contextual Teaching and Learning (CTL) atau pembelajaran kontekstual dalam mempelajari Hukum Newton Ketiga. Metode yang digunakan dalam penelitian ini adalah weak experiment yang diimplementasikan kepada 24 siswa kelas VIII di sekolah international. Pengumpulan data menggunakan rubric Creative Product Analysis Matrix (CPAM) dan pengumpulan data respon siswa menggunakan questionnaire. Analisa data menunjukkan bahwa siswa mengikuti CTL sebagai pembelajaran dalam mempelajari Hukum Newton Ketiga. Lebih lanjut, hasil dari kreativitas siswa di sekolah tersebut dalam kategori rata - rata. Respon siswa terhadap implementasi CTL juga mendapatan respon yang positive dalam semua indicator. Ini menunjukkan bahwa implementasi CTL cocok untuk siswa dalam mempelajari Hukum Newton Ketiga dan CTL bisa memicu kreativitas siswa SMP.